Insulation of Building Envelope Complicated Node Points - Leshchenko, Maryna; Semko, Oleksandr; Shumska, Liubov; Filonenko, Olena (International Journal of Engineering and Technology, 2018)
The article describes typical structural parts of building insulation, which significantly affect reduced thermal resistance. It analyzes flaws in calculation and construction of the described elements and provides further development of engineering calculation methods of building envelope when studying their difficult elements. Real values of linear heat transmission of building envelope difficult node points are calculated in the paper. It has been found that theoretical and experimental research of temperature and humidity conditions of difficult for thermal modernization structures (balconies, beam joints, cornices, foundation zones, thermally conductive inclusions etc.) enables the development of practical recommendations for avoiding localized condensation, mould growth, frost cracks. It is recommended to provide insulation continuity when developing energy efficient structural designs of building insulation.Â Â Â